Decreased hepatic accumulation and enhanced esterification of cholesterol in mice deficient in mdr1a and mdr1b P-glycoproteins - Gary D. Luker; Julie L. Dahlheimer; Richard E. Ostlund, Jr.; David Piwnica-Worms (Journal of Lipid Research, 2001)
Class I P-glycoproteins [Pgp; MDR1 (ABCB1) in humans, mdr1a and mdr1b in mice] confer resistance to structurally diverse chemotherapeutic drugs in cultured cells and intact animals, but the function of these proteins in normal physiology remains poorly characterized. Based on studies in cell culture, a putative role for class I Pgp in absorption and intracellular trafficking of sterols has been proposed. We examined wild-type and mdr1a −/−/1b −/− mice to determine whether class I Pgp affects cholesterol absorption and esterification in vivo. Using a dual-isotope protocol, absorption of orally administered radiolabeled cholesterol into serum did not differ between wild-type and mdr1a −/−/1b −/− mice, demonstrating that class I Pgp is not essential for overall absorption of cholesterol through the intestine. However, the ratio of oral to intravenous labeled cholesterol in liver was decreased significantly in mdr1a −/−/1b −/− mice. In the liver, but not other tested organs, deletion of class I Pgp enhanced kinetics of esterification of an oral bolus of radiolabeled cholesterol without affecting esterification of cholesterol administered intravenously. Steadystate hepatic content of cholesterol and esterified cholesterol also were unaffected by absence of mdr1a and mdr1b. Thus, in normal animals, class I Pgp functions to kinetically increase hepatic accumulation and decrease esterification of orally administered cholesterol in vivo. —Luker, G. D., J. L. Dahlheimer, R. E. Ostlund, Jr., and D. Piwnica-Worms. Decreased hepatic accumulation and enhanced esterification of cholesterol in mice deficient in mdr1a and mdr1b P-glycoproteins.